Influence Of Foliar Application Of Fenugreek And Licorice Root Extract On Growth And Yield Of Onion Plants (Allium Cepa L.) (Journal of Pharmaceutical Negative Results, 2023)
This experiment was carried out at the horticulture fields of technical college of Akre, on onion plants during season (2021-2022), to study the effect three factor the first one using three levels of fenugreek (0.0, 5.0 and 10.0 g l-1), and second factor using three levels of licorice root extract (0.0, 4.0 and 8.0 g l-1) on growth and yield of onion. The results showed the plants treated with 10.0 g l-1 of fenugreek extracted had significantly influenced on plant height, fresh leaves weight, bulb weight, and total yield. While, foliar spraying of licorice root extract at level 8.0 g l-1 significantly increased plant height, bulb length, bulb diameter, bulb weight, and total yield. In addition, the interaction between among the two factors studied, indicated that the plants which sprayed with 5.0 g l-1 fenugreek interacted with 8.0 g l-1 of licorice root extract gave the highest value of bulb diameter, bulb weight, and total yield. It appears that using those levels gave the best growth and yield results on onion plants. Further research is needed to investigate whether the higher concentrations than used in this research will give the better parameters